Sintesis dan Identifikasi Biodiesel dari Transesterifikasi Refined Palm Oil dengan Ko-pelarut Metil Ester - Elvianto Dwi Daryono; Rini Kartika Dewi; Dwi Ana Anggorowati (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
The transesterification of refined palm oil (RPO) with methyl ester (FAME) as a cosolvent was investigated to enhance solubility and mass transfer, thereby accelerating the reaction and improving biodiesel yield. This study aimed to evaluate the effects of FAME co-solvent concentration and reaction time on the transesterification process of RPO. The reaction was conducted using 250 g of RPO with a molar ratio of oil to methanol of 1:6, 0.8 wt% KOH catalyst, a stirring speed of 100 rpm, and a reaction temperature of 70°C. The co-solvent concentration was varied from 0% to 15%, while the reaction time ranged from 5 to 30 minutes. The reaction was carried out in a two-neck flask, followed by distillation to remove impurities. The resulting product was analyzed using gas chromatography and physical property tests. The optimum conditions were achieved at 5% FAME co-solvent concentration and a reaction time of 30 minutes, yielding a crude biodiesel yield of 99%, a FAME concentration of 999,265 mg/L, and a density of 0.88 g/mL, which meet the biodiesel quality standard SNI 7182:2015. The use of FAME as a co-solvent improves process efficiency by eliminating the need for a co-solvent separation step at the end of the reaction.